Faktor-Faktor yang Mempengaruhi Pemanfaatan Teknologi Informasi terhadap Kinerja Individual pada KPP Pratama Kota Padang - Elsa Afriyanti; Yeasy Darmayanti; Yunilma Yunilma (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2019)
Nowadays, the role of information technology has developed rapidly. Directly, technology can affect individual performance in completing their work at the company. So, information technology has a strategic role in organizations and individuals. The purpose of this study is to find the effect of social factors, “affect”, complexity, task suitability, and conditions that facilitate individual performance in Padang Primary Tax Office. The population in this study are all tax officers who work at KPP Pratama Padang. The sampling method is purposive sampling. Based on research findings, it is found that social factors and future consequences have a significant effect, while “effect”, task complexity, and facilitating conditions do not have significant results on individual work.